Analysis of the initial fraction of Békésy recordings in the threshold audiometry* - JAROSZEWSKI, Antoni; RAKOWSKI, Andrzej (Archives of Acoustics, 1976)
Statistical analysis of initial transients in the threshold Békésy tracings, observed mostly at higher rates of the signal level control (i.e. 10 dB /s and 30 dB /s), is given. The transients reach several dB and last about 10 s. Possible background of psychological nature is discussed.